2003
DOI: 10.2165/00128072-200305050-00002
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance Syndrome in Children

Abstract: The simultaneous presence of various cardiovascular risk factors in the same individual is not rare, even in the pediatric age group. The clustering of risk factors can be termed insulin resistance syndrome (IRS) because of the putative central role of tissue insulin insensitivity in the background of the inter-related metabolic disturbances. Fasting hyperinsulinemia, impaired glucose tolerance, dyslipidemia, and hypertension are considered to represent the basic abnormalities of IRS. The most prevalent relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 92 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Likewise increased hepatic lipase activity can account for the rise in high-density lipoprotein depuration, producing hypoalphalipoproteinemia [31]. However, the high prevalence of low C-HDL levels observed in this study is one of the highest reported in the literature [13,30,32].…”
Section: Discussionmentioning
confidence: 73%
“…Likewise increased hepatic lipase activity can account for the rise in high-density lipoprotein depuration, producing hypoalphalipoproteinemia [31]. However, the high prevalence of low C-HDL levels observed in this study is one of the highest reported in the literature [13,30,32].…”
Section: Discussionmentioning
confidence: 73%
“…It is well-documented that sedentary lifestyle is associated with childhood obesity [28]. In our study, physical activity was linked to WC, as an anthropometric measure of abdominal obesity.…”
Section: Discussionmentioning
confidence: 89%
“…Insulin also enhances triglyceride (triacylglycerol) synthesis in liver and adipose tissues, increases the breakdown of circulating lipoproteins by stimulating lipoprotein lipase activ- ity in adipose tissues, and suppresses lipolysis both in adipose tissues and in muscles. 23,24 …”
Section: Discussionmentioning
confidence: 99%